The comic allegory as scenic artifice in the choreographic works of Quasar Cia. de Dança (1989-1992) (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
This article analyzes the scenic works of Quasar Cia. de Dança in its first five years, especially in the period between 1989 and 1992. The aim of the study is to investigate historically, the details of the process of the configuration of humor as a scenic resource that characterized the works of the company from Goiania. For this purpose, the research makes use of choreographic works, interviews and articles published in the written press as historical sources. The analysis of these documents is guided by theories of dance studies, history and art history.
Keywords: Dance history; Comic allegory; Quasar Cia de Dança; Humor; Dance